2020
DOI: 10.1101/2020.08.05.20168666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paediatric Attendances and Acuity in the Emergency Department during the COVID-19 Pandemic

Abstract: Aim: To investigate the difference in both numbers and acuity of presentations to the Paediatric Emergency Department (PED) during the peak time period of the current global SARS-CoV-2 pandemic. Design: This single centre retrospective observational study used routinely collected electronic health data to compare patient presentation characteristics between 21st March and 26th April 2020 compared to the equivalent time period in 2019. Results: There was a 90% decrease in attendances to PED, with a 10.23% redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Reductions in hospital admissions in COVID-19 studies ranged from 31%-75% in Italy, 26,27,38 45.0% in France, 91 45-60% in Finland, 34 and 68% in the USA 24 to 85.7% in the UK. 42 Another Italian study reported that admissions fell 9.5% in the weeks preceding lockdown (when schools closed) and 30.7% during full lockdown. 26 The proportions of ED presentations admitted during lockdown rose 13.2% in the UK 42 and 15.8% in USA 24 for ward admissions and 5.8% (1.9, 10.0) for paediatric intensive care in the UK, 42 with an Italian study reporting a 164% rise in the proportion of ED presentations admitted.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Reductions in hospital admissions in COVID-19 studies ranged from 31%-75% in Italy, 26,27,38 45.0% in France, 91 45-60% in Finland, 34 and 68% in the USA 24 to 85.7% in the UK. 42 Another Italian study reported that admissions fell 9.5% in the weeks preceding lockdown (when schools closed) and 30.7% during full lockdown. 26 The proportions of ED presentations admitted during lockdown rose 13.2% in the UK 42 and 15.8% in USA 24 for ward admissions and 5.8% (1.9, 10.0) for paediatric intensive care in the UK, 42 with an Italian study reporting a 164% rise in the proportion of ED presentations admitted.…”
Section: Resultsmentioning
confidence: 98%
“…Eight were from China, 45,50,68,70,72-74,77 7 from other low and middle-income countries (LMIC; Turkey, 58,79 Pakistan, 25 India, 28,65 Brazil, 55 Bangladesh 76 ) and 13 from Italy, 23,26,27,32,35,38,49,56,78,81,84-86 21 from the UK, 22,29-31,37,39-42,44,47,48,54,60,62-64,69,87,89,90 12 from the USA, 24,43,46,51,57,59,66,67,71,75,92,94 and 1 study each from Ireland, 88 France, 91 Germany, 93 Greece, 80 Spain, 61 Finland, 34 Slovenia, 33 Israel, 82,83 Australia, 52 Canada 53 and Japan. 36…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations